COMPARISON OF FINANCIAL PERFORMANCE OF CONVENTIONAL BANKING AND SHARIA BANKING USING CAMEL ANALYSIS DURING THE COVID-19 PANDEMIC - Sanjaya, Rama Arya; Suripto, Suripto; harori, m.ikbal (Jurnal Kompetitif Bisnis, 2022)
ABSTRACT The purpose of this study is to determine the difference in the financial performance of Conventional Banks and Islamic Banks during the COVID-19 pandemic using CAMEL analysis, namely the Capital aspect includes the Capital Adequacy Ratio (CAR), Asset quality includes Non Performing Loans (NPL), Management includes Net Profit Margin ( NPM), Earning includes Return On Assets (ROA), Liquidity includes Loan To Deposit Ratio (LDR). This type of research is comparative using quantitative methods. The sample in this study using purposive sampling method amounted to 16 banks, namely 8 conventional banks and 8 Islamic banks. The data collection technique is in the form of documentation in the form of company financial statements listed on the website of the Financial Services Authority. The data analysis technique used is descriptive analysis, normality test using the Kolmogorov Smirnov statistical test and the Wilcoxon signed rank test statistical test and hypothesis testing using multiple discriminant analysis (MDA) statistical tests using SPSS 25.0. The results of this study indicate that there is an insignificant difference between the financial performance of Conventional Banks and Islamic Banks during the COVID-19 pandemic using NPL and LDR with a significance value of 0.921 and 0.843, respectively. Then three variables show that there are significant differences between the financial performance of Conventional Banks and Islamic Banks during the COVID-19 pandemic using CAR, NPM and ROA with a significance value of 0.026, 0.000 and 0.048, respectively. Keywords: Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Net Profit Margin (NPM), Return On Asset (ROA), Loan To Deposit Ratio (LDR).